Management of Online Learning in Islamic Higher Education: Challenges and Prospects - M. Nurul Ikhsan Saleh; Ratna Sari; Pujiarti Pujiarti (POTENSIA: Jurnal Kependidikan Islam, 2023)
During the Covid-19 pandemic, the implementation of online learning at Islamic universities faced numerous challenges and required opportunities for improvement. Based on the perspectives of students at universities that combine synchronous and asynchronous models, this study aims to analyze the challenges and prospects for improving management of online learning using Google Classroom and Zoom. This study is a qualitative case study of the course of Islamic Education Learning in Schools for sixth semester students in the Islamic Education study program. In July 2021, the researcher conducted interviews with 53 men and women. This study discovered that students face online learning challenges such as being unmotivated, undisciplined, losing concentration, feeling burdened, difficult to understand, noninteractive, disturbed by domestic work, unmanageable time, unmanageable team, and a lack of internet signal. This study, on the other hand, discovered opportunities for improving online learning implementation, such as increasing personal motivation, developing self-discipline, ice breaking and quizzes, simple tasks, note-taking and listening, learning media variation, effective communication with parents, time management, small group instruction, and lecture recordings. The findings of this study will be useful in improving the implementation of online-based learning at universities during the Covid-19 pandemic to ensure the quality of the teaching and learning process.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//